Miggy buddy: a household-level food waste management innovation using maggot bioconversion for a zero waste future / Muhammad Emilson ... [et al.] - Emilson, Muhammad; Jeffrosson Purba, Rasya Theresa; Daffa, Muhammad Akram; Hanif, Muhammad; Hidayatulloh, Rendi Syarif (Universiti Teknologi MARA, Kedah, 2024)
"Miggy Buddy" is an innovative household-scale solution designed to address the challenges of organic waste management through bioconversion using Black Soldier Fly (BSF) larvae. This kit, equipped with tools, media for maggot breeding, and an interactive consultation website, effectively reduces organic waste by up to 56%. Additionally, the product includes ecoenzyme to prevent unpleasant odors. With the increasing volume of organic waste in Indonesia, "Miggy Buddy" offers an environmentally friendly and efficient approach to processing organic waste, aligning with public interest in sustainable waste management.